Factors Influencing the Decision-Making Processes of Chinese Graduate Students to Study in Thailand: A Grounded Theory Approach - Zheng, Zhiyuan; Buarabha, Homhuan; Sriruksa, Arunee; Syers, Sikarnmanee (Journal of Spatial Development and Policy, 2025)
This study investigates the motivations and decision-making processes of Chinese graduate students in selecting Thailand as their study destination, utilizing a grounded theory approach. Data were collected through in-depth interviews with 40 master’s and doctoral students from Khon Kaen University and Chiang Mai University. The analysis revealed two primary categories of motivations: internal and external. Internal motivations include study impressions, individual experiences, career status, and future aspirations, reflecting personal growth and career development needs. External motivations encompass study abroad observations, environmental factors, policy frameworks, and social influences, highlighting the role of external conditions in shaping decisions. Findings indicate that external motivations, particularly the study abroad environment and policy support, play a dominant role in influencing students’ decisions, while internal motivations focus on personal development goals. This research provides insights into the multifaceted nature of study abroad decisions and contributes to understanding the dynamics of international talent mobility. The findings also offer practical implications for policymakers and educational institutions in improving support for international students.